2016
DOI: 10.1115/1.4031772
|View full text |Cite
|
Sign up to set email alerts
|

TRICO II Core Inventory Calculation and its Radiological Consequence Analyses

Abstract: Two severe accident scenarios are investigated in this paper as they have never been considered previously in the safety analysis report (SAR) of the Congo TRIGA Mark II research reactor (TRICO II) in Kinshasa, the Democratic Republic of Congo. The source term is derived from the reactor core after two postulated accidents: (1) a large plane crash with total destruction of the reactor building and (2) full damage of one fuel element while the reactor building remains intact. Total effective dose (TED), after c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The human body dose was obtained by ingestion or inha- lation process, which takes into account the metabolism of radioisotopes in the body, type and level of energy of the emitted radiations, and radio-sensitivity of the organs. 29 It was observed that the calculated CEDE are lower, and the highest value primarily affects the thyroid followed by the skin, and thirdly the lungs. 12 The maximum value for this organ is about 7.0 • 10 −1 mSv occurring at a distance of 0.5 km from the source with arrival time of six minute, and it is about 4.1 • 10 −2 mSv at 5 km from the source with arrival time of 01 h : 05 min.…”
Section: Organ Committed Effective Dose Equivalent Results and Analysismentioning
confidence: 96%
“…The human body dose was obtained by ingestion or inha- lation process, which takes into account the metabolism of radioisotopes in the body, type and level of energy of the emitted radiations, and radio-sensitivity of the organs. 29 It was observed that the calculated CEDE are lower, and the highest value primarily affects the thyroid followed by the skin, and thirdly the lungs. 12 The maximum value for this organ is about 7.0 • 10 −1 mSv occurring at a distance of 0.5 km from the source with arrival time of six minute, and it is about 4.1 • 10 −2 mSv at 5 km from the source with arrival time of 01 h : 05 min.…”
Section: Organ Committed Effective Dose Equivalent Results and Analysismentioning
confidence: 96%